Strategi Pesan Persuasif di Media Sosial Instagram @somethincofficial - Cinthya Tania; Vina Benita Laksono (Avant Garde, 2022)
Social media is a tool used for various activities, including supporting business and marketing. Small and medium industries tend to choose to use Instagram to communicate with young and productive consumers, the majority of whom are similar to the characteristics of these social media users. SOMETHINC is a local skincare and beauty brand made in Indonesia that actively uses Instagram to interact with its consumers. This study aims to analyze how communication messages in SOMETHINC's Instagram social media can affect consumers' cognitive processes in making choices to use products based on central and peripheral concepts in the Elaboration Likelihood Model theory. Based on the Elaboration Likelihood Model developed by Petty and Cacioppo (1983), the central pathway is a pathway that encourages individual behavior change after going through a process of careful and wise consideration of the benefits of information provided as an advocacy effort. Meanwhile, the peripheral pathway explains that behavior change occurs without going through a process of careful consideration of the benefits of the information conveyed and is more influenced by some exciting signs, cues, or sources in persuasion efforts to encourage behavior change. This research method uses a digital ethnographic method with the primary data source in the form of documentation of the Instagram account @somethincofficial. The results show that SOMETHINC has used strategies according to the four pillars of social media and persuasive communication messages according to the central and peripheral pathways in the Elaboration Likelihood Model. This study concludes that the Elaboration Likelihood Model approach can help brands design more effective social media strategies to adapt persuasive messages to the intended audience.